2015
DOI: 10.3390/ijms16011980
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thymic Epithelial Cells and Central Tolerance in Autoimmune Hepatitis Development: Novel Perspective from a New Mouse Model

Abstract: Autoimmune hepatitis (AIH) is an immune-mediated disorder that affects the liver parenchyma. Diagnosis usually occurs at the later stages of the disease, complicating efforts towards understanding the causes of disease development. While animal models are useful for studying the etiology of autoimmune disorders, most of the existing animal models of AIH do not recapitulate the chronic course of the human condition. In addition, approaches to mimic AIH-associated liver inflammation have instead led to liver tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 107 publications
(173 reference statements)
0
13
0
Order By: Relevance
“…We previously generated conditional knockout mice in which Traf6, a known regulator of mTEC development, was specifically deleted in TECs using FoxN1-Cre knock-in mice (Traf6ΔTEC mice) [14, 19]. Deletion of Traf6 in TECs led to a marked reduction in the numbers of mature mTECs and a 50% reduction in the numbers of tTregs [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously generated conditional knockout mice in which Traf6, a known regulator of mTEC development, was specifically deleted in TECs using FoxN1-Cre knock-in mice (Traf6ΔTEC mice) [14, 19]. Deletion of Traf6 in TECs led to a marked reduction in the numbers of mature mTECs and a 50% reduction in the numbers of tTregs [19].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, results from a related study did not support a role for CD8α + cDCs in tTreg cell production [13]. In addition, while defective antigen expression and presentation by mTECs results in autoimmunity development in mice and humans [14, 15], the role of tDCs in the development of peripheral autoimmunity is controversial [16, 17]. While Ohnmacht et al showed that DC depletion led to impaired negative selection and fatal autoimmunity, Birnberg et al found normal negative selection and no autoimmune manifestations following DC ablation.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, thymic medullary TECs (mTECs) express different self-antigens to eliminate auto-reactive T-cells (central tolerance) and regulate the production of regulatory Tcells (Tregs). These Tregs work peripherally to dampen the immune response (peripheral tolerance) [22] .…”
Section: Immunologymentioning
confidence: 99%
“…AIH is a chronic immune-mediated liver disease characterized by hepatitis, the presence of autoantibodies and elevated IgG [1] . Histological features include portal inflammation and interface hepatitis along with lymphocytic infiltrates of both B-and T-lymphocytes [2] . AIH, unlike PBC and PSC, is classically very sensitive to immunosuppression.…”
mentioning
confidence: 99%
“…and a high Ki67 proliferation index [80 %, whereas in A thymomas the Ki67 proliferation index was low (\80 %) [56]. These observations might be related to the findings that tumor TEC as neoplastic counterparts of normal TEC may promote thymocyte proliferation and differentiation through the elaboration of cytokines and chemokines and that thymomas have the capacity to promote the intratumoral maturation of T cells from immature precursors [115][116][117][118][119][120][121][122].…”
Section: Expression Of Cell Cycle and Apoptosis Regulators In Thymic mentioning
confidence: 95%